Analisis Merger Bank Syariah Indonesia (BSI) dengan Pendekatan Maslahah Mursalah - Nasruddin Mohammad, Sultan Antus; Agilga, Olla Triana (Tasyri' : Journal of Islamic Law, 2022)
Sharia banks are not a new thing in Indonesia, since the emergence of Bank Muamalat Indonesia in 1991, other banks began to pave the way in Sharia’s world. Although it has been for a long time, the Sharia bank is not as smooth as the convencional banks that have been existed. The market share is relatively small if compared with number of muslims in Indonesia. Until now, in order to strengthen sharia banking, the government has taken action by merging 3 BUMN banks, those are BRI Syariah, Mandiri Syariah, and BNI Syariah. The merger action is expected to produce good synergies, so that it can offset convencional banks even more. Large capital assets can encourage sharia banking to provide financing to the community, so it can help increase the growth of sharia economy in Indonesia. Also hoped to improve the economy of sharia in Indonesia and to penetrate the global market by bringing in more innovative and creative products from sharia that could compete globally. The methods used in this study are library research and nature of the study are descriptive analysis. The objective of the study is to analyze the amount of malshah produced by the merger. The findings of this study explain that according to the maslahah side, merger’s actions do more harm than mudharat. The problems posed in the form of increasing the sharia economic sector in Indonesia, the strength of capital owned, and can compete nationally even global.